2011
DOI: 10.1152/ajpcell.00500.2010
|View full text |Cite
|
Sign up to set email alerts
|

High-energy phosphate transfer in human muscle: diffusion of phosphocreatine

Abstract: The creatine kinase (CK) reaction is central to muscle energetics, buffering ATP levels during periods of intense activity via consumption of phosphocreatine (PCr). PCr is believed to serve as a spatial shuttle of high-energy phosphate between sites of energy production in the mitochondria and sites of energy utilization in the myofibrils via diffusion. Knowledge of the diffusion coefficient of PCr (D PCr) is thus critical for modeling and understanding energy transport in the myocyte, but DPCr has not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
33
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 50 publications
7
33
0
Order By: Relevance
“…D can be calculated from the two signals measured without and with diffusion weighting, S 0 and S , by D=1b[],log(),S0log(),S. Then the standard deviation of D from error propagation, σD2, can be given by σD2=1b2{},σs2[],logS0S0+σs2[],logSS=1b2[],σsS02+σsS2 …”
Section: Technical Considerations Of Diffusion Mrs Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…D can be calculated from the two signals measured without and with diffusion weighting, S 0 and S , by D=1b[],log(),S0log(),S. Then the standard deviation of D from error propagation, σD2, can be given by σD2=1b2{},σs2[],logS0S0+σs2[],logSS=1b2[],σsS02+σsS2 …”
Section: Technical Considerations Of Diffusion Mrs Experimentsmentioning
confidence: 99%
“…where σ s is the standard deviation of the noise in S 0 and S . Assuming that f is the fraction of the time for acquiring S 0 , ψ the SNR per TR of the S 0 experiment, and N the total number of excitations in the combined experiment (the S 0 experiment + the S experiment), the relative error of ADC measurement can be given by σDD=1f+ebD1fNψbD. …”
Section: Technical Considerations Of Diffusion Mrs Experimentsmentioning
confidence: 99%
“…In situations where, without localized mitochondrial ATP production, diffusion limited high energy phosphate carriers do not adequately supply ATP needs, synaptic function may degrade. In striated muscle, the diffusion distance over the half-life of phosphocreatine has been estimated at ~66 μm (Gabr et al, 2011). If this finding can be extended to neurons with processes on the order of millimeters in length, it may explain why disruption of the mitochondrial dynamics machinery manifests in neurons with long processes as neuropathies.…”
Section: Mitochondrial Dynamics In Neuronal Development and Synaptmentioning
confidence: 99%
“…Furthermore, due to the tissue ultrastructure the diffusion is not isotropic, i.e., not equally fast in all directions. Diffusion anisotropy of water has been observed in brain white matter , spinal cord , skeletal muscle , as well as the heart wall . The diffusion of water in muscle tissue was investigated to study biomechanical effects of muscle tissue on water diffusion , to examine the structure of human muscle in detail or to estimate the robustness of diffusion MRI in the clinic .…”
Section: Introductionmentioning
confidence: 99%
“…Already early on, Moonen with coworkers measured the ADC of ATP, PCr and inorganic phosphate (P i ) in rat muscle . De Graaf et al added diffusion tensor spectroscopy and Gabr et al reported the diffusion tensor‐derived properties of PCr in human muscle. Kruiskamp, in his PhD thesis , was the first to also use proton MR spectroscopy to investigate the ADC of total creatine (Cr) in muscle.…”
Section: Introductionmentioning
confidence: 99%